2017
DOI: 10.1016/j.bbabio.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of thylakoid membranes in terminal heterocysts and vegetative cells from two cyanobacteria, Rivularia M-261 and Anabaena variabilis, by fluorescence and absorption spectral microscopy

Abstract: Heterocyst is a nitrogen-fixing cell differentiated from a cell for oxygen-evolving photosynthesis (vegetative cell) in some filamentous cyanobacteria when fixed nitrogen (e.g., ammonia and nitrate) is limited. Heterocysts appear at multiple separated positions in a single filament with an interval of 10-20 cells in some genera (including Anabaena variabilis). In other genera, a single heterocyst appears only at the basal terminal in a filament (including Rivularia M-261). Such morphological diversity may nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…This misconception stems partly from early investigations, where harsh isolation methods unintentionally damaged the photosynthetic enzymes more than the nitrogenase, and resulted in the misunderstanding that heterocysts are brownish rather than green in color and completely lacking in chlorophyll- a fluorescence emission [21]. More recently, single cell spectroscopy has shown that heterocysts emit chlorophyll- a (Chl- a ) fluorescence to lower but still comparable levels, as in vegetative cells [18,22]. Intact PSII complexes have been found in heterocysts from the cyanobacterium Nostoc punctiforme (PCC 73102/ATCC 29133, henceforth referred to as N. punctiforme ).…”
Section: Enzymes In the Heterocyst Thylakoidsmentioning
confidence: 99%
“…This misconception stems partly from early investigations, where harsh isolation methods unintentionally damaged the photosynthetic enzymes more than the nitrogenase, and resulted in the misunderstanding that heterocysts are brownish rather than green in color and completely lacking in chlorophyll- a fluorescence emission [21]. More recently, single cell spectroscopy has shown that heterocysts emit chlorophyll- a (Chl- a ) fluorescence to lower but still comparable levels, as in vegetative cells [18,22]. Intact PSII complexes have been found in heterocysts from the cyanobacterium Nostoc punctiforme (PCC 73102/ATCC 29133, henceforth referred to as N. punctiforme ).…”
Section: Enzymes In the Heterocyst Thylakoidsmentioning
confidence: 99%
“…By means of known reference spectra, this equation can be solved for the intensities of each pigment. The reference spectra can either be loaded from a spectra database, or from literature [40][41][42][43][44], or directly extracted from the lambda stack. Obtained linear unmixing function will generate a multi-channel image, in which each channel represents only one pigment.…”
Section: Spectral Imaging and Spectral Unmixingmentioning
confidence: 99%
“…These have been applied in studying the effects of altering various physicochemical factors such as light and nutrient supply, on T. variabilis phototrophic or heterotrophic growth. A large number of studies have investigated T. variabilis growth rate as a function of time, cell density, or photosynthesis components, but only a few have directly surveyed the interrelation between multiple parameters. Such data can be used for modeling growth kinetics.…”
Section: Physico‐chemical Factors Affect T Variabilis Biomass Producmentioning
confidence: 99%